Commuting patterns of secondary school students in the functional urban region of Budapest - Keserű, Imre (Hungarian Geographical Bulletin, 2013)
Children's regular travel to school is the third most important travel purpose in Hungary. While commuting to school has been studied from several aspects, there has been little research carried out on the differences in demand for and supply of schools in the functional urban region (FUR) of Budapest. The objective of this study is to explore the potential imbalance between demand for secondary education and the supply of schools within the social activity space of education in the functional urban region of Budapest and analyse the regional patterns of the resulting commuting. An expansion of the definition of commuting to daily travel to school is suggested based on the fundamental similarities to commuting to work. The analysis is carried out on two levels combining municipality level and household data from a household survey in the functional urban area of Budapest. The results show that the increasing imbalance between regional demand and supply has led to a spatial imbalance within the functional spatial structure of education. The inconsistency between demand and supply has been growing in the past 20 years and resulted in more intensive commuting. The pattern of commuting has not changed, though. As opposed to commuting to work, the dominance of Budapest as a commuting destination has increased. A connection between commuting characteristics and the educational qualifications of the parents, family income and car ownership has also been demonstrated. The results show that socio-economic changes due to suburbanisation in the functional urban area might lead to increasing commuting to Budapest and to a growing car use.